EFEK SINERGIS KLOROKUIN DAN N-ACETYL CYSTEINE TERHADAP PENURUNAN PARASITEMIA DAN PENURUNAN KADAR MALONDYALDEHYDE ERITROSIT MENCIT YANG DIINFEKSI PLASMODIUM BERGHEI - Iskandar, Agustin; Sudjari, Sudjari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Malaria is still a global health problem around the world particularly in Indonesia. Chloroquine is one of the anti-malarial drugs which is still used in Indonesia. The aim of this research is to know the synergic effect of Chloroquine and N-Acetyl Cysteine towards parasitemia and erythrocyte malondyaldehyde levels in mice infected with Plasmodium berghei. This was an experimental research using Plasmodium berghei and BALB/c strain mice, 6−8 weeks old, with body weight 20−30 grams. After infected with Plasmodium berghei, the mice were divided into eight (8) groups: control, chloroquine, NAC 0.25 mg/gBb; NAC 0.5 mg/gBb; NAC 1 mg/gBb and combined drugs of chloroquine and NAC 0.25 mg/gBb; NAC 0.5 mg/gBb; NAC 1 mg/gBb. On the 3rd, 5th, and 7th day after treatment, the mice were killed and their parasitemia and Malondialdehyde (MDA) levels were measured. By using MANOVA and Tukey HSD test, a signifi cant difference in parasitemia level was found between the control and chloroquine group, as well as the control and combined drug groups. In the NAC groups, there was no decrease. The decrease of MDA level began on the 7th day. It can be concluded that there was a synergic effect between the chloroquine and N-Acetyl Cysteine in decreasing parasitemia and malondyaldehyde levels in mice BALB/c infected with Plasmodium berghei.